Evaluación de la resistencia al pasador del fruto neoleucinodes elegantalis y caracterización morfoagronómica de germoplasma silvestre de lycopersicon spp. (2006)
COMPENDIO En un diseño de bloques completos al azar con tres repeticiones se evaluaron diez materiales de L. hirsutum, dos de L. peruvianum y uno de L. esculentum cv maravilla (testigo). El 60.3% de los frutos fueron afectados por N. elegantalis en el testigo; mientras que en las accesiones de L. hirsutum y L. peruvianum ningún fruto fue afectado. Todas las accesiones silvestres presentaron resistencia de campo. Los coeficientes de variación de los descriptores cuantitativos usados en la evaluación morfoagronómica, fluctuaron entre 22.88 y 51.89%. El análisis de clasificación con los descriptores cuantitativos, permitió la conformación de cuatro grupos y de tres con los cualitativos. Palabras claves: descriptores, Neoleucinodes elegantalis, materiales. ABSTRACT Resistance evaluation to the fruit borer N. elegantalis and Morphoagronomic characterization in wild germplasm of Lycopersicon spp. The percentage of affected fruits with borer .N. elegantalis in the control treatment (L. esculentum cv maravilla) was of 60.3%; whereas in all the evaluated maternals of wild species L. hirsutum and L. peruvianum, none fruit was affected by this plague insect. All the wild materials of Lycopersicon spp showed a resistance of fieldâ€? to the fruit borer. The variation coefficients of the quantitative descriptors used in the morpho agronomic evaluation fluctuated between 23.02 and 58.40%, indicating that thet genetic potential available in this germplasm evaluated for breeding programs, depends on the character that it'is looking to improve. The analysis of classification with quantitative and qualitative descriptors allowed with both the formation of four and three groups in wich the similar genetic constitution of the materials in each group was the probable cause of the obtained classification. Key words: Lycopersicon wild species descriptors, genetic constitution. Neoleucinodes elegantalis